Nationalism on Social Media: The impacts of comments on ASEAN Football Pages on mental health - Perdana, Rangga Cipta; Gempita, Genta Iverstika (GHMJ (Global Health Management Journal), 2024)
Background: As a modern communication medium, Facebook provides a new place to people who live far apart to interact and discuss on the same topic, such as football. This research examines how the nationalism is generated through Facebook. From the perspective of social realities, Facebook is observed as a channel of communication utilized by football lovers. However, communication through Facebook also causes conflicts among its users. Aims: This study aims to investigate how nationalism is expressed through communication on Facebook and how conflicts affect mental health but can also build and perpetuate a sense of nationalism and strengthen group identities. Methods: To achieve the objectives, content analysis is used to examine the manifestation with regard to the context of generating a spirit of nationalism through the communication interaction process of Facebook users. Data collection in this study was conducted through ASEAN football page on Facebook. Posts, images and comments left under the related posts were then selected when they are regarding only the spirit of nationalism. Results: Results show that Facebook is not only a social medium but also, a means of generating nationalism through conversations. As nationalism is expressed both in a positive and negative way on ASEAN football page, it, of course, leads to conflicts because of the differences in the orientation of values and interest when the conflicting sides hold different background.   Conclusion: By exploring how nationalism is expressed through Facebook comments on ASEAN football page, the research provides insights into how digital platforms shape and amplify nationalistic sentiments. This understanding is crucial in an era where social media plays a significant role in public discourse and it also highlights the mental health impacts of online nationalistic comments. This is significant for developing strategies to address and mitigate the negative psychological effects that such interactions can have on individuals.   Received: 31 July 2024, Reviewed: 4 August 2024, Revised: 22 August 2024, Accepted: 24 August 2024.